Pengaruh Perencanaan Terhadap Peningkatan Nilai Akreditasi MTs Al-Amiriyyah Blokagung Tegalsari Banyuwangi - Ribut Suprapto; Muhammad Balya Khajjan (Institut Agama Islam Darussalam Blokagung, 2020)
This researching is directed at 4 main points, namely: (1) Planning of Al-Amiriyyah Islamic junior high school Blokagung Tegalsari Banyuwangi 2018/2019; (2) Increasing the accreditation value of Al-Amiriyyah islamic junior high school Blokagung Tegalsari Banyuwangi 2018/2019; (3) indluence of planning on increasing the accreditation value of Al amiriyyah islamic junior hihg school Blokagung Tegalsari Banyuwangi 2018/2019; (4) How much influence does planning have on increasing the accreditation value of Al-Amiriyyah islamic junior high school Blokagung Tegalsari Banyuwangi 2018/2019. This researching uses quantitative descriptive methods. Product moment analysis is used in the data validity test and to find the reliability of the data using the Alpha formula, while in the hypothesis test using the F test and T test. Then the data analysis uses a simple linear regression model. The population of the researching is 37 teachers of Al-Amiriyyah islamic junior high school Tegalsari Banyuwangi, To measure variables, researchers uses questionnaires for planning and accreditation. After analyzing the data , it was found that the influence of planning on increasing the accreditation value of Al-Amiriyyah islamic junior high school Blokagung Tegalsari Banyuwangi 2018/2019 is 78%, the remaining 22% is influenced by another variables.